Pengujian UU No. 27 Tahun 2009 Dan UU No. 17 Tahun 2014 Tentang MPR, DPR, DPD & DPRD (MD3) Sebagai Upaya DPD Untuk Mengembalikan Kewenangan Konstitusionalnya - Suparto Suparto (UIR Law Review)
In Law No. 27 of 2009 on the People's Consultative Assembly (“MPR”), House of Representatives (“DPR”), Regional Representative Council (“DPD”), and Provincial Legislative Council (“DPRD”) (“MD3),a lot of DPD’s authorities are being reduced. It made the DPD filed a judicial review to the Constitutional Court; in which by its ruling No. 92/PUU-X/2012 restored the authorities of DPD back to where it was – in line with the 1945 Constitution. In spite of the decision, DPR still issued Law No. 17 of 2014 on MD3 (which is a replacement for the Law No. 27 of 2009), with the same content concerning DPD’s authorities. DPD filed another judicial review, which was granted by the Constitutional Court with the ruling No. 79/PUU-XII/2014. The ruling, once more, restored the authorities of DPD. Yet DPR still ignored the ruling by not accommodating it in their Code of Conduct. In the future, DPR and the President - as state’s institutions holding regulatory authority - should comply to any of Constitutional Court’s ruling, since it has the same level with the Law.